Highly efficient biosynthesis of l-ornithine from mannitol by using recombinant Corynebacterium glutamicum. (May 2021) - Sheng, Qi; Wu, Xiaoyu; Jiang, Yan; Li, Zhimin; Wang, Fei; Zhang, Bin
Graphical abstract: Highlights: C. glutamicum was first applied for producing l -ornithine from mannitol. Adjusting mtlD expression promote the conversion from mannitol to l -ornithine. Overexpression of pfkB improved l -ornithine production from mannitol. Abstract: Mannitol is a promising six-carbon sugar alcohol that is widely found in macroalgae. The potential of mannitol as a renewable raw material is of interest due to the advantages of ocean farms. Herein, the biobased production of l -ornithine from mannitol was resoundingly demonstrated for the first time in engineered Corynebacterium glutamicum S9114 through the deletion of the mannitol repressor MtlR. By modulating the expression of mtlD and reinforcing the fructose metabolic pathway, we generated the strain MTL13 that produced 54.56 g/L of l -ornithine with a yield of 0.47 g/g on mannitol. These results illustrate the robust conversion from mannitol to l -ornithine using engineered Corynebacterium glutamicum, providing a reference for the biobased production of additional chemicals from mannitol.